PENYAMAKAN ATASAN SEPATU (UPPER SHOES) TNI AD DARI KULIT KERBAU (BUBALUS BUBALIS) SEBAGAI ALTERNATIF PENGGANTI BAHAN BAKU KULIT SAPI - Titik Anggraini (Politeknik ATK Yogyakarta, 2014)
Shoes are generally made of chrome tanned cow hide. The leather tannery industry has not utilized buffalo leather as raw material for the tanning of shoes leather, especially upper shoes military. This research is a preliminary study to determine whether buffalo skin can be used as an alternative raw material for making military boots that meet the standards of military upper shoes which are made of cow leather. Stages of the process and tanning method are generally equal to the tanning process that uses upper cow hide shoes (Beam House, Tanning, Post Tanning, and Finishing). Buffalo skin as much as 3 pieces, which is being processed before, are split into 6 sides and then processed together in a drum by using mineral tanning materials that are chromosal B; retanning vegetable material, resin acrylic, oil fatliquoring anionic and anionic dyes. After the tanning process is completed, the physical and organoleptic testing that include tanning test, paint lid scrub resistance (dry and wet), tensile strength, elongation, water absorption, strength flexibility, zwik durability, and reliability spark are tested with the test method in accordance to ISO 0234.22009. From the test results, the criteria subsequently matched with Standards/Technical Specification of Field Black Shoes with Lemon Pattern Number: 20-2-16024 April 2006. Therefore, it can be concluded that buffalo leather has the same physical properties and organoleptic with cow hide after processing (tanned) by the method of upper shoe tanning so that it can be use das an alternative raw material.